Bombardier beetles of genus Brachinus Weber, 1801 (Carabidae: Brachininae: Brachinini) from India - Akhil, S.v.; Divya, M.; Sabu, K. Thomas (Zootaxa, 2020)
Brachinus devagiriensis sp. nov. is described from the Western Ghats, a global hot spot of biodiversity in southwest India. Detailed diagnostic features of the 27 species of Indian Brachinus with a key to the species are provided.